Nilai-Nilai Moral Kisah Nabi Adam As Di Dalam Al-Qur’an - khoiriyah, siti maftukhatul,; Syafii, Sufyan (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to determine the explanation of verses reletad to the story of creation and the story of Prophet Adam AS descent on this earth, as well as the moral values of the story Prophet Adam AS that can be applied in social life. This type of research is descriptive qualitative in the form of library research. This study uses a qualitative method whit a historical approach. The data collection technique in this research is documentation. The documentation that the author uses as a primary sourse is the book Shahih Qashash al-Qur’an creation Dr. Hamid Ahmad Thahir, while for secondary sources, namely books, literature, and reading related to the story of Prophet Adam AS. From the research it was found that Prophet Adam AS was the first human being created by Allah SWT from the soil. Apart from that, some of the verses of the al-Qur’an also explain that the creation of human descendants of Prophet Adam AS came from nuthfah. Allah SWT gave the task and responsibility to Prophet Adam AS and his descendants as abdillah and caliph on earth. The moral values contained in the story of the Prophet Adam AS are; humble, fair, encouragement to study, gratitude and help, advice to stay away from arrogant and belittling others, advice to be careful with devil’s tempatation, advice to immediately repent for mistakes made, forgiving, petience and tawakkal, as well as advice to avoid jealousy and resestment. Keyword: The story of Prophet Adam AS, The Caliph, and Moral Value.